Youth engagement and resilience against violent extremism in the Sahel - United Nations Interregional Crime; Justice Research Institute (Freedom from Fear, 2020)
On the sidelines of the 74th session of UNGA, on 24 September 2019, UNICRI, the International Centre for Counter-Terrorism (ICCT) and the Global Center on Cooperative Security (the Global Centre) - in collaboration with the Danish Ministry of Foreign Affairs and the Permanent Mission of Senegal to the United Nations - organised a panel on the critical role that youth play across the Sahel in preventing and countering violent extremism.